Innovative Strategies for Improving the Engagement of Online Music-Ensemble Classes Through Flipped Teaching - Yi-Li Chang; Mohd Nasir Hashim (Wacana Seni Journal of Arts Discourse, 2024)
The COVID-19 pandemic prompted educators to design online-teaching methods to conduct class activities. However, not all subjects are suitable for online delivery, especially if they require practical activities. One example is music-ensemble classes. Online music-ensemble classes have long faced the problem of poor audio latency and sound quality. Furthermore, being unable to play musical instruments together can easily disrupt students’ concentration. A virtual strings workshop with 60 secondary school students was held to examine the effectiveness of learning processes in this context. Flipped teaching was employed to compare with traditional, lecture-based teaching in music-ensemble classes. A survey and interviews were used, followed by critical analysis and discussion. The study aimed to attract the attention of music-ensemble instructors to a new teaching strategy—flipped teaching—to obtain greater interaction and engagement, and better learning results. The findings show that the flipped teaching approach benefitted students’ learning outcomes and mindsets and reduced the problems of poor audio latency and distraction. Furthermore, flipped teaching inspired and improved learning motivation. This article provides the teaching concept, details of the process, and suggestions for a new teaching method. Innovative delivery methods, such as podcasts and virtual concerts, can also enhance students’ learning environments and positive educational outcomes.